Effect of Mulches, Reflectant and Type of Seed Bed on Yield of Barley (Hordeum Vulgare) Grown Under Semi - Arid Conditions - Ali, Masood; Prasad, Rajendra (Annals of Arid Zone, 2016)
A field experiment was conducted for two years at the Indian Agricultural Research Institute, New Delhi to study the direct and combined effects of seed bed types (flat and ridge-furrow) and mulches (straw, dust and 110 mulch) applied on fallow land during monsoon ( Khan!) season and various mulches (straw, stover. dust and FYM) and kaolin antiperspirant applied in standing crop during post-monsoon (rabi) season on barley yield under semi-arid conditions. Mulches significantly increased soil moisture and thereby the barley yield. Plat seed bed gave higher yield than ridge-furrow bed. Different mulches and reflect ant applied in standing crop increased straw and grain production considerably, Straw mulch was better than all other mulches and reflectant. In the first year of the experiment dust mulch was second to straw but in the second year its effectiveness was considerably less. Foliar spray of kaolin water emulsion also significantly increased the barley yield over control. Highest yield of barley was recorded when straw mulch was applied on flat beds during monsoon period and again in standing crop of barley.